5x-3+13=4+y

Simple and best practice solution for 5x-3+13=4+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+13=4+y equation:


Simplifying
5x + -3 + 13 = 4 + y

Reorder the terms:
-3 + 13 + 5x = 4 + y

Combine like terms: -3 + 13 = 10
10 + 5x = 4 + y

Solving
10 + 5x = 4 + y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 5x = 4 + -10 + y

Combine like terms: 10 + -10 = 0
0 + 5x = 4 + -10 + y
5x = 4 + -10 + y

Combine like terms: 4 + -10 = -6
5x = -6 + y

Divide each side by '5'.
x = -1.2 + 0.2y

Simplifying
x = -1.2 + 0.2y

See similar equations:

| 6(-3n+5)=-6(4-6n) | | 7y^2-y+4=0 | | 5r=16 | | -14.9u+12.7u-9.74=-6.04-1.7u | | 5.9-b= | | -8(1-4x)+3x=35x+63 | | 8x-7=f(x-2) | | xyz+xyt+yzt+xzt=xyzt(x+y+z+t) | | -8(1-4x)+3x=35x+6 | | 5x+2-10=-2(x+3) | | 13-p=-5 | | 2(y+3)-4y=-6 | | (-2-4)2x+y=-8 | | -8=1.6m | | 2h+12=68 | | 4(2-b)=12 | | 11(2x)+7x=870 | | -4(8+3m)-8=-(6m-2) | | (x-4)2=25 | | -7x-2x+10x+3x=48 | | 5.25-6.75= | | 41n(x+7)=20 | | 9y^2-2x+7=0 | | 8(-0.25+0.25c)-2c=-2 | | 4y-2-2y=10 | | 15-24a=30 | | 4(2.5+1.75b)+7b=10 | | -4p=.667 | | 20=12+4x | | 15.3s=14.2s-18.92 | | 10-2x=2+x | | 5.25-x=-1.5 |

Equations solver categories